Specifying and Verifying Holonic Multi-Agent Systems Using Stochastic Petri Net and Object-Z: Application to Industrial Maintenance Organizations - Mazigh, Belhassen; Abbas-Turki, Abdeljalil (IntechOpen, 2012)
None